Ethnographic Trailblazers: Herodotus, Thucydides and Xenophon - Prus, Robert; Burk, Matthew (Qualitative Sociology Review, 2010)
While ethnographic research is often envisioned as a 19th or 20th century development in the social sciences (Wax 1971; Prus 1996), a closer examination of the classical Greek literature (circa 700-300BCE) reveals at least three authors from this era whose works have explicit and extended ethnographic qualities. Following a consideration of “what constitutes ethnographic research,” specific attention is given to the texts developed by Herodotus (c484-425BCE), Thucydides (c460-400BCE), and Xenophon (c430-340BCE). Classical Greek scholarship pertaining to the study of the human community deteriorated notably following the death of Alexander the Great (c384-323BCE) and has never been fully approximated over the intervening centuries. Thus, it is not until the 20th century that sociologists and anthropologists have more adequately rivaled the ethnographic materials developed by these early Greek scholars. Still, there is much to be learned from these earlier sources and few contemporary social scientists appear cognizant of (a) the groundbreaking nature of the works of Herodotus, Thucydides, and Xenophon and (b) the obstacles that these earlier ethnographers faced in developing their materials. Also, lacking awareness of (c) the specific materials that these scholars developed, there is little appreciation of the particular life-worlds depicted therein or (d) the considerable value of their texts as ethnographic resources for developing more extended substantive and conceptual comparative analysis. Providing accounts of several different peoples’ life-worlds in the eastern Mediterranean arena amidst an extended account of the development of Persia as a military power and related Persian-Greek conflicts, Herodotus (The Histories) provides Western scholars with the earliest, sustained ethnographic materials of record. Thucydides (History of the Peloponnesian War) generates an extended (20 year) and remarkably detailed account of a series of wars between Athens and Sparta and others in the broader Hellenistic theater. Xenophon’s Anabasis is a participantobserver account of a Greek military expedition into Persia. These three authors do not exhaust the ethnographic dimensions of the classical Greek literature, but they provide some particularly compelling participant observer accounts that are supplemented by observations and open-ended inquiries. Because the three authors considered here also approach the study of human behavior in ways that attest to the problematic, multiperspectival, reflective, negotiated, relational, and processual nature of human interaction, contemporary social scientists are apt to find instructive the rich array of materials and insights that these early ethnographers introduce within their texts. Still, these are substantial texts and readers are cautioned that we can do little more in the present statement than provide an introduction to these three authors and their works.